Learning with Graffiti: Spanish Students Facing the Tabooed Linguistic Landscape - Fainstein, Paula Elizabeth (Cuadernos de Lingüística Hispánica, 2023)
During academic exchanges, students are in contact with the linguistic landscape (LL). In this paper, we aimed to characterize the linguistic attitudes of Spanish as SL or FL students towards the linguistic taboo (LT). For that, we collected samples of tabooed signs detected inside the restrooms of a university. The data was in surveys of students who were in face-to-face or online language immersion. With the samples collected, we describe the tabooed LL with which those who carried out the face-to-face exchange were in contact. The results of the surveys made it possible to investigate the students’ knowledge of tabooed expressions in Spanish and, in addition, to characterize their linguistic attitudes towards LT. We conclude that the students, although they show a predisposed linguistic attitude to deal with LT, lack the communicative competence that would allow them to be competent users in relation to taboo expressions. Thus, this type of experience justifies the need to include the LT as part of the contents of the Spanish as a SL or FL class.